ANALISIS KINERJA KEUANGAN DENGAN METODE Z-SCORE UNTUK MEMPREDIKSI FINANCIAL DISTRESS PADA PT. JAMKRIDA RIAU PEKANBARU - Asyuni, Nila; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the prediction of financial distress as an analysis of the financial performance of PT. Jamkrida Riau Pekanbaru in 2015 to 2020 using the ratio of net working capital to total assets, retained earnings to total assets, earnings before interest and tax to total assets, book value of equity to book value liabilities and z-score. The type of research conducted in the form of secondary data which is data from financial statements. Data collection techniques used are interviews and documentation studies. The data analysis technique used is to calculate the ratios contained in the z-score method. Based on the results of the financial data analysis of PT. Jamkrida Riau that the level of net working capital to total assets from 2015 to 2020 has decreased every year. The level of retained earnings to total assets in 2015 to 2020 has increased and decreased every year. The level of earning before interest and tax to total assets in 2015 to 2020 also increases and decreases every year. The level of book value of equity to book value of liabilities in 2015 to 2020 has decreased every year. The results of the analysis of the z-score calculation in 2015 to 2020 can be categorized that PT. Jamkrida Riau Pekanbaru has a very good financial condition and is far from financial distress. Keywords: Financial Performance, Z-Score and Financial Distress